Intracardiac thrombosis: frequency, risk factors and place of oral anticoagulants in treatment - E. S. Kropacheva («REMEDIUM GROUP» Ltd., 2020)
This review systematizes the currently known data on intracardiac thrombosis. The main nosology leading to left atrial thrombosis is atrial fibrillation, with up to 90% of all trombi forming in the left atrial appendage. The optimal method to diagnose thrombosis is the transesophageal echocardiography. The detection rate of left atrial appendage thrombosis in early studies ranged from 2.5 to 74.7% and dropped to 1-15.2% in the era of oral anticoagulants. However, there is no basis for performing transesophageal echocardiography as a screening examination for all patients with atrial fibrillation, and the CHA2DS2-VASc clinical scale is the guideline for prescribing and selecting antithrombotic therapy. The article presents data on the possibility of lysis of the left atrial appendage thrombosis against the background of oral anticoagulants therapy, which is of practical importance for patients before cardioversion and pulmonary vein ablation. The results of published studies and observations of patients receiving vitamin К antagonists show that 46.3-85% of thrombi are dissolved. The only prospective study to investigate the possibility of left atrial thrombosis lysis in patients with atrial fibrillation or fluttering while taking direct oral anticoagulants was X-TRA, which studied rivaroxaban therapy and showed thrombi dissolution in 41.5% of patients. The frequency of left ventricular thrombosis in patients with acute coronary syndrome with ST segment elevation in the age of reperfusion therapy is about 6-7%, reaching 19.2% in patients with anterior myocardial infarction and reduction of left ventricular ejection fraction. These recommendations indicate that only vitamin К antagonists may be prescribed in patients with left ventricular thrombosis. However, the results of the COMMANDER HF study showing the potential of rivaroxaban to prevent thromboembolic complications in patients with chronic heart failure have laid the foundation for the use of direct oral anticoagulants in left ventricular thrombosis. At present the study of efficacy and safety of apixaban and rivaroxaban in this category of patients is ongoing, but there are no results at present. In most cases, right ventricular thrombosis is part of the development of a pulmonary embolism, and much less often it accompanies right ventricular arrhythmogenic dysplasia or is associated with implantable devices. Anticoagulants are the basis for the treatment of these patients, and the present guidelines allow for moderate and low risk thromboembolism in patients with pulmonary artery thromboembolism, along with parenteral anticoagulants, prescribing immediate oral anticoagulants, giving preference to Xa-factor antagonists or direct thrombin inhibitors.